Ang ikaklit sa aming hardin Ikaklit in our garden - Neri, Bernadette Villanueva (Raintree Trading and Publishing Inc., 2012)
This book dared to discussed the nurturing relationship of a lesbian couple and their aspiration to build a family. This book deserves to be celebrated for its power to raise consciousness. Its main symbol is the garden - a sanctuary and space for healing wounded emotions. This is also the main virtue of the book - to promote human rights, love and understanding.